2016
DOI: 10.3846/bjrbe.2016.35
|View full text |Cite
|
Sign up to set email alerts
|

Effects of extended short-term aging duration on asphalt binder behaviour at high temperatures

Abstract: Many factors affecting pavement performance include variations in binder composition and environmental conditions during asphalt mixture production. Hence, predicting pavement performance is a difficult task. This paper aims to investigate the effects of short term aging on binder viscosity at high temperature. In order to predict the effects of short term aging on the asphalt binder viscosity at high temperatures, a Response Surface Method was performed on the Rotational Viscometer test results. An experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…This indicates that stiffer binders are harder to be compacted due to their higher viscosity, which directly affects mixtures' volumetric properties. This finding is in agreement with the results outlined by [13,35]. According to the results, the maximum CEI, V a , VMA, and VFA of mixtures produced using binder A80 are 57.2, 3.7%, 12.6%, and 75.2%, respectively, while the corresponding values of mixtures produced using binder B80 are 42.5, 3.3%, 14.5%, and 81.2%.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This indicates that stiffer binders are harder to be compacted due to their higher viscosity, which directly affects mixtures' volumetric properties. This finding is in agreement with the results outlined by [13,35]. According to the results, the maximum CEI, V a , VMA, and VFA of mixtures produced using binder A80 are 57.2, 3.7%, 12.6%, and 75.2%, respectively, while the corresponding values of mixtures produced using binder B80 are 42.5, 3.3%, 14.5%, and 81.2%.…”
Section: Discussionsupporting
confidence: 92%
“…Literature shows that aging stiffens the binders and negatively affects their viscosity, which makes the pavement more prone to distress types, such as cracking and raveling [11,12]. Hamzah and Omranian (2016) proved a significant increment in binders' viscosity by extending the aging duration for 100 min compared to the standard duration (85 min) of a rolling thin-film oven testing (RTFOT) used for simulating short-term aging [13]. Recent studies tend to focus on the effect of temperature used in standardized short-and long-term simulations and their role in rheology and chemistry [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of aging on binders were evaluated from the differences between their un-aged and aged rheological properties. The Rolling Thin Film Oven (RTFO) was used to produce a homogenous artificial short-term age asphalt binder following the procedures outlined by Hamzah and Omranian (2016) [10]. To prepare mixtures, binders and batched aggregates with fillers were mixed at a temperature between 160 °C and 170 °C (based on the viscosities obtained from the Rotational Viscometer test).…”
Section: Methodsmentioning
confidence: 99%
“…Hamzah et al (2015) utilized the RSM to study the effects of elongated short-term aging on the rheological properties of binder at intermediate temperatures [9]. Hamzah and Omranian (2016) studied the effects of aging on the asphalt binder behavior at high temperatures by applying RSM [10]. Saha and Biligiri (2017) used RSM to optimize the asphalt mixtures fracture toughness characteristics that affect cracking performance [11].…”
Section: Introductionmentioning
confidence: 99%
“…Hamzah et al [ 20 , 21 ] investigated the influences of recycled aggregate content, compaction temperature and asphalt content on volumetric and mechanical properties of asphalt mixture for optimizing the binder content based on the CCD of RSM. Furthermore, Hamzah et al [ 22 ] found that statistical models based on RSM can predict the effects of aging on binder viscosity behavior at high temperatures effectively. Khodaii et al [ 23 ] employed RSM to evaluate the effects of lime content and gradation on ITS and its ratio of asphalt mixture under dry and saturated conditions.…”
Section: Introductionmentioning
confidence: 99%